THE PLAN’S ANALYSIS OF FLEXIBLE BENEFITS CONCEPT IMPLEMENTATION TOWARDS THE BABY BOOMERS, X, AND Y (MILLENIALS) GENERATIONS - Bayu Ade Candra; Andri Winata; Anuar Sanusi (Prosiding International conference on Information Technology and Business (ICITB), 2018)
The flexible benefits concept has been widely adopted by a lot of companies around the world. This research examined whether the concept was relevant to be applied in one of the companies in Indonesia that business on agroindustry, whereas the company has owned various employees through generation such as; Baby Boomers, X, and Y generation (millennials generation).Qualitative approach was applied in this research. Therefore, the instrument of the data was obtained by doing observation, interview, and documentation. The data analysing process wasdone in several steps; accumulating, reducting, and serving the data, also concluding the result. Moreover, the result of this research was explained descriptively and will be tested through credibility, transferability, dependability and confirmability test. The result of this research showed that the Baby Boomers, X, and Y generation employees apreciate the concept since it provides them with benefits they need. Indeed, however, it is suggested that if the concept, flexible benefits are effective and efficient, before be implemented in certain company, the management team should support it as well as Compensation and Benefits Departement (CB) should educate their staff deeply about  the concept in order to be applied well.keyword: Flexible benefits; Gen X; Gen Y; Millenials; Baby Boomers